The Effect of Organizational Culture, Motivation and Organizational Commitment on Employee Performance: The Case of Coal Handling and Transportation Unit of PT. Bukit Asam Tbk. Tanjung Enim - Benni Irawadi; Abid Djazuli; Choiriyah Choiriyah (International Journal of Marketing & Human Resource Research, 2026)
The purpose of this study is to determine the effects of organizational culture, work motivation, and organizational commitment on employee performance in the Coal Handling and Transportation Unit of PT. Bukitasam, Tbk, Tanjung Enim Mining Unit. This study is a causal associative study using a quantitative approach. The population used in this study comprised all employees of the Coal Handling and Transportation Division of PTBA UPTE, totaling 152. The sample used a purposive sampling technique with a Slovin formula of 111 respondents. The study's results indicate that organizational culture, motivation, and organizational commitment influence employee performance in the Coal Handling and Transportation Unit of PT. Bukit Asam Tbk, Tanjung Enim Mining Unit, both partially and simultaneously